A gestão democrática nos planos municipais de educação no Rio Grande do Sul: evidências, interpretações e contradições - Lauer, Munir José (2017)
This dissertation presents the democratic management (action, concept, practice) expressed in 497 municipal education plans in the State of Rio Grande do Sul. It investigates how democratic management was described in municipal education plans, in the form of the law. Through a bibliographical review and empirical work, it was proposed to come out the evidences, interpretations and contradictions of the municipal education plans, comparing them with the National Education Plan and the State Education Plan. The process of the data production was done through the information available in the website pne.mec.gov.br/planosde-educacao/situacao-dos-planos-de-educacao, in the legislations of the 497 municipalities of Rio Grande do Sul, and consequently in their municipal plans. The analysis focused, specifically, on goal 19 about democratic management. The data produced were organized into ten categories of analysis: demonstrative of the National Education Plan on democratic management terminology in the form of the law and in the annex of the law; demonstrative of the State Education Plan on democratic management terminology in the form of the law and in the annex of the law; municipalities and their respective laws regarding municipal plans; content found in municipal plans different than those mentioned in the National Education Plan and in the State Education Plan, as to democratic management; municipalities that make no mention of democratic management in the law that creates the municipal education plan; municipalities that indicate (in a decisive way) in their municipal plans the creation or regulation of municipal law on democratic management in the education system; municipalities that present in the municipal plans goals and strategies that mix (or contradict) the National Education Plan and the State Education Plan, in relation to democratic management (mainly regarding the provision of directors); municipalities that suggest in their municipal plans only the democratic provision (direct election) for the position of the director in a public school; relationship between creation and regulation of municipal law on democratic management and indication of the direct election for directors by the school community; comparative of th e municipal education plans of the twenty largest municipalities and the twenty smallest municipalities, in Rio Grande do Sul, regarding democratic management. It is possible to affirm that the education plans of the 497 municipalities in the state of Rio Grande do Sul were based, sometimes at the national plan, sometimes at the state education plan, or as a third way in relation to the subject. The democratic management in municipal plans configures sometimes biased to meritocracy, technique, managerialism and business logic, and sometimes participatory, representative, political and contrary to the market bias.